The Composition of Emissions from Sanding Corian® with Different Sandpapers - Seungkoo Kang; Huayan Liang; Yong Qian; Chaolong Qi (Aerosol and Air Quality Research)
Abstract Laboratory tests were conducted to characterize the composition of emissions from sanding Corian®, a solid-surface composite material mainly composed of alumina trihydrate (ATH) and acrylic polymer. Three sandpaper materials (ceramic, silicon carbide, and aluminum oxide) were tested to distinguish the contribution of aluminum-containing dust in the emission from Corian® and sandpaper itself. The result can help identify the main cause of the pulmonary fibrosis from exposure to aluminum-containing dust while sanding Corian®. Airborne dust samples were measured using direct-reading instruments and collected using a Micro-Orifice Uniform Deposit Impactor (MOUDI) for estimating the normalized dust generation rate. The size-classified dust samples from MOUDI were analyzed for elemental aluminum content. Additionally, air samples were analyzed for characterizing methyl methacrylate (MMA). The results from the direct-reading instruments reveal that the size distribution of particulate from sanding Corian® differs from that of sawing Corian®, showing that the size distribution of dust is affected by the fabrication process. The normalized respirable dust generation rate indicates that more respirable dust was generated during sanding Corian® board. However, the use of aluminum oxide sandpaper does not result in a higher aluminum content in the respirable dust from sanding Corian®, suggesting that the aluminum content of the respirable dust is primarily originated from Corian® itself. The generation rates of MMA from sanding did not vary much among all types of sandpapers, and they were much lower than that of sawing, likely due to the higher temperature in the sawing process.